Genital trauma due to coital injury in women at Pikine National Hospital: epidemiological, diagnostic, and therapeutic insights from 32 cases - Moussa, Diallo; Ababacar, Gueye K.; Aziz, Diouf A.; Youssoupha, Touré; Mouhamet, Sene; Anna, Dia; Alassane, Diouf (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Sexual trauma involves very different situations in women, most of which are uncommon in clinical practice. These are, often minor lesions following “normal” sexual act, not requiring medical attention. In general, it is estimated at less than 1% of gynecological emergencies. Methods: This is a retrospective, descriptive and analytical study which extends over a period from March 2019 to January 2023, i.e., a duration of 3 years and 10 months. Results: During the study period, 32 cases of per coital trauma were collected out of a total of 18,924 gynecological and obstetrical emergencies, i.e., a frequency of 0.16%. The 20–40-year-old age group was the most represented with a rate of 72.7% and most of them were married (72.7%). The trauma occurred during consensual sexual intercourse with a male, rate of 75.8% compared to 24.2% of non-consensual reports. It was the first sexual act in 69.7% of cases and mainly occurred at night (72.7%). Patients mainly consulted for vaginal bleeding. The relationship between the type of lesion and parity as well as that between the type of lesion and the circumstances of occurrence showed that complex lesions were more frequently encountered in nulliparous women during consensual sexual act. Conclusions: Percoital genital trauma in women remains an under-reported condition despite the enormous risks to the vital, but also functional and psychological prognosis.